BASOTHO WOMEN’S MINORITY - Maqelepo, Sehlomeng Dorothy (My University, 2011)
The past two decades have seen a drastic turn in Lesotho’s economy. The loss of South African mining opportunities for Basotho workers and Structural Adjustment Programmes (SAPs), which, among others caused a huge shedding of government employees; left many families without stable incomes. This has resulted in a large number of people, particularly women, entering into business as the only available alternative; be it formal or informal trading. However, it became evident that many women face challenges; because of their cultural minority status, making it difficult for many women to enter into some of the businesses. The purpose of this study was to find out whether women do have challenges, if they do what they are and what they are doing to start, and remain in business. The findings highlight that women’s minority status do not stop them from entering into business, it only hinders them from getting into some businesses; licensing and land acquisition issues are still preventing them from entering into some types of businesses; they still require spouse’s approval and this seemed to be a challenge to some women. iii It became evident that there is a long road ahead for women if they are to address the situation because their representation in economic decision making bodies and chambers is low; meaning their voice is low. It is promising to find out that however difficult, women are fount in many types of businesses and most of their businesses are vibrant, though small. Their dealings with banks are pleasant. Many women are aware of their cultural challenges and feel customary law is outdated and must be eliminated.
MM - P&DM
Keywords: Customary law, Lesotho; Women - minority status, Lesotho; Micro businesses, Lesotho